(untitled) (Bangladesh Journal of Neurosurgery, 2020)
Background: Health care workers are most frequently suffering from lower back pain. Objective: The purpose of the present study was to determine the prevalence and the effects of low back pain among health care providers working in Dhaka city. Methodology: This descriptivecross sectional study was conducted in Department of Neurosurgery at National Institute of Neurosciences & Hospital, Dhaka, Bangladesh from July 2012 to June 2013 for a period of one (1) year. The physicians and nurses who were working in the public hospital at any age group of both male and female were selected as study population. The details of the history of the physicians and nurses regarding their life style, hour of practising, and the mode of work and so on were asked in face to faced interview. A survey was carried out to174 conveniently selected participants to be filled and completed. Both descriptive and inferential tests were reported. Result:A total number of 117 medical professional were recruited from 5 hospital in Dhaka city. Majority medical professionals were from BSMMU (48.0%).The majority study subjects were mentioned that they had spent 6 to 12 hours every day for work which was 92(53.8%). Most of the respondents mentioned that the working environment was very good to fair. The prevalence of low back pain was found in almost every respondents which was 113(66.1) subjects. Interestingly most of the respondents were clearly stated that the LBP was occurred after joining in the work. In this study majority of the respondents were given the history of localized low back pain which was 86(76.1%) subjects. Moderate intensity of pain was reported by most of the respondents which was 67(59.3%) subjects. Intermittent nature of pain was mostly recorded which was 70(61.9%) subjects.There were several individual and profession risks factors were retrieved from the respondents. Many study subjects were given the answer about lifting objects or patients from bed to bed or wheel chair which was 55(48.7%) subjects. About 91(80.5%) respondents had said that pain was due to bad body posture. Conclusion: In conclusion most of the medical professionals are suffering from moderate intensity lower back pain after joining of their job Bang. J Neurosurgery 2020; 9(2): 135-141